MENINGKATKAN KETERLIBATAN SISWA DENGAN TEKNOLOGI SEBAGAI ALAT PEMBELAJARAN INTERAKTIF - Intan Qurrota Aini; Noraziza; Aidatin Nufus; Khalida Nabila Agustin; Ahmad Suriansyah; Maimunah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low involvement of students in the conventional learning process which tends to be passive and less interesting. The purpose of this study is to analyze the effectiveness of the use of technology as an interactive learning tool in increasing student participation and learning motivation. The methodology used is literature study and observation limited to technology-based learning practices in several classes, focusing on the use of educational applications, online learning platforms, and interactive media such as videos and simulations. The results of the study show that the application of technology is able to create a more dynamic learning environment, increase student interaction with materials, and encourage collaboration between students. Additionally, technology allows teachers to provide quick feedback and provide more personalized learning. Overall, the use of technology as an interactive learning tool has proven to be effective in improving student engagement and learning quality.